Article IN VITRO STUDY OF Vitex gardneriana SCHAUER TOXICITY ON Artemia salina AND ITS EFFECT ON EGGS AND LARVAE OF Haemonchus contortus (Veterinária Notícias, 2022)
This research aimedto investigate the toxic action of Vitexgardneriana on microcrustacean Artemiasalina by using hydroalcoholic extract fromleaves (EHF) and acute toxicity test (CL50)concentrations of 100, 500, 1.000, 10.000,20.000, and 50.000/mL. Sodium hypochlorite(NaClO) at 1% was used as positive control,and saline and 1% DMSO were used asnegative control. Vitex gardneriana showedlow toxic potential, with 50% mortality inthe microcrustacean metanauplii population(concentration: 34.600 mg/mL). A. salina isa seawater microcrustacean widely used inbioassays for determining the toxic dose ofbioactive substances because of its low costsand its related simple, aseptic procedures. Todetermine the toxic action of the hydroalcoholicextract of V. Gardneriana on eggs and larvaeof Haemonchus contortus, 2,5mL of EHF witha concentration of 34,600 mg/mL were addedinto single-species nematode fecal culturescontaining approximately 12.000 eggs. Only26,6% of the eggs hatched, correspondingto an EHF efÀ ciency of 73,3%, whereas thehatchability was 50% in control, with 6.000larvae recovered. The À ndings show thepotential of this plant as an alternative inparasite control.